Localized Scleroderma: A Clinical Review - Tratenberg, Mark; Gutwein, Farrah; Rao, Varuni; Sperber, Kirk; Wasserrman, Amy; Ash, Julia (Current Rheumatology Reviews, 2017)
Localized scleroderma (LS) is characterized by excessive collagen deposition leading to thickening of the dermis, subcutaneous tissue or both. The outcome for most patients with localized scleroderma is directly related to the type and stage of the affected tissue. The major challenge for untreated patients is not increased mortality risk, rather deformity and growth defects from skin, muscle and bone abnormalities. Treatment is individualized to type and stage of the lesion and may include pharmacologic and non-pharmacologic therapies. Among the pharmacologic modalities, methotrexate with systemic glucocorticoids is currently the mainstay of treatment. More controlled trials are needed to determine the length of treatment and the maintenance dose of this combination therapy.
Keywords: non-pharmacologic therapies